Dysfunction of annexin A2 contributes to hyperglycaemia-induced loss of human endothelial cell surface fibrinolytic activity - Dai, Haibin; Yu, Zhanyang; Fan, Xiang; Liu, Ning; Yan, Min; Chen, Zhong; Lo, Eng H.; Hajjar, Katherine A.; Wang, Xiaoying (Thrombosis and Haemostasis, 2013)
Hyperglycaemia impairs fibrinolytic activity on the surface of endothelial cells, but the underlying mechanisms are not fully understood. In this study, we tested the hypothesis that hyperglycaemia causes dysfunction of the endothelial membrane protein annexin A2, thereby leading to an overall reduction of fibrinolytic activity. Hyperglycaemia for 7 days significantly reduced cell surface fibrinolytic activity in human brain microvascular endothelial cells (HBMEC). Hyperglycaemia also decreased tissue type plasminogen activator (t-PA), plasminogen, and annexin A2 mRNA and protein expression, while increasing plasminogen activator inhibitor-1 (PAI-1). No changes in p11 mRNA or protein expression were detected. Hyperglycaemia significantly increased AGE-modified forms of total cellular and membrane annexin A2. The hyperglycemia-associated reduction in fibrinolytic activity was fully restored upon incubation with recombinant annexin A2 (rA2), but not AGE-modified annexin A2 or exogenous t-PA. Hyperglycaemia decreased t-PA, upregulated PAI-1 and induced AGE-related disruption of annexin A2 function, all of which contributed to the overall reduction in endothelial cell surface fibrinolytic activity. Further investigations to elucidate the underlying molecular mechanisms and pathophysiological implications of A2 derivatisation might ultimately lead to a better understanding of mechanisms of impaired vascular fibrinolysis, and to development of new interventional strategies for the thrombotic vascular complications in diabetes.
Keywords: Annexin A2; hyperglycaemia; fibrinolytic activity; advanced glycation end-product; human brain microvascular endothelial cells